RECEPTION ANALYSIS OF PONTIANAK YOUTH TO ‘NGONDEK’ MALE IN MS.QUEEN VARIETY SHOW - Widha Anistya Suwarso; Dewi Utami; Rikka Anggraini maulida (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2022)
The emergence of micro-celebrities and their competition in attracting followers requires them to have a certain persona. Ngondek is one of the personalities that many celebrities choose in providing personal branding for themselves. The popularity of micro-celebrity is fostered by the media by inviting these celebrities to appear on television shows. This phenomenon gives the impression that gondek is a shortcut to becoming viral and famous. It is feared that children and adolescents, as well as adults with limited literacy skills, will imitate this. Through this research, the researcher tries to find out the audience's reception of content that promotes gondek behavior. The results of the study show that informants tend to gravitate toward preferred reading for representation of professional entertainers. The informants are in a negotiated reading position for representation of femininity. Men performing feminine are cute and entertaining because they are supported by several determining factors such as the script and the actor's natural abilities. The informant is in an oppositional reading position for the representation of the object of the joke, remembering morally, making someone the object of a joke is not an act that can be justified. Regarding the representation of LGBT in the research text, informants who hold a negotiated reading position believe that there are many men with feminine performances who are physically fit but do not try to promote LGBT to their audiences.